The benefits of social media as a modern teaching and learning tool in higher education in Indonesia - Martunis, Martunis (Accentia: Journal of English Language and Education, 2020)
This paper explores the benefits of social media for assisting teaching process in higher education institution in Indonesia. The paper also looks at the ways of using social media such as Facebook, Twitter, and WeChat. As the continuous growing of social platforms, most students and teachers in higher education level are now interacting through social media. The opportunities to utilize them as teaching and learning tools are endless. This paper reveals that the use of social media had positive outputs towards teaching and learning. However, social media also comes with some challenges which may limit its effectiveness. Thus, some possible solutions will be presented here in order to make the most out of social media for teaching and learning.